2017
DOI: 10.5935/1518-0557.20170012
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-all cycle in reproductive medicine: current perspectives

Abstract: The freeze-all strategy has emerged as an alternative to fresh embryo transfer (ET) during in vitro fertilization (IVF) cycles. Although fresh ET is the norm during assisted reproductive therapies (ART), there are many concerns about the possible adverse effects of controlled ovarian stimulation (COS) over the endometrium. The supra-physiologic hormonal levels that occur during a conventional COS are associated with modifications in the peri-implantation endometrium, which may be related to a decrease in pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 33 publications
(53 reference statements)
0
40
0
1
Order By: Relevance
“…Fresh embryo transfer (ET) is still the standard procedure for in-vitro fertilization (IVF) treatments, although recent scientific data have shown the potential benefit of performing cycle segmentation with deferred ET, known as the freeze-all policy [2][3][4][5][6] . It is unknown whether this strategy can be used for all patients, irrespective of their ovarian response and hormone levels during controlled ovarian stimulation (COS) [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Fresh embryo transfer (ET) is still the standard procedure for in-vitro fertilization (IVF) treatments, although recent scientific data have shown the potential benefit of performing cycle segmentation with deferred ET, known as the freeze-all policy [2][3][4][5][6] . It is unknown whether this strategy can be used for all patients, irrespective of their ovarian response and hormone levels during controlled ovarian stimulation (COS) [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The new analysis included 259 IVF cycles with blastocyst embryo transfers in normal and high responders; nonetheless, they found that FTET had a 31 per cent higher clinical pregnancy rate than FET. 5 however, time to pregnancy was not reported in any study. Additionally, they suggested that FTET lowered the OHSS risk for at-risk women with low-quality evidence (OR 0.24, 95 per cent CI 0.15-0.38; 1633 women; I 2 = 0 per cent; lowquality evidence).…”
mentioning
confidence: 84%
“…Although evidence of FTET after electively freezing all embryos has been suggested to have good outcomes through basic and clinical research, the results of recent clinical studies still challenge the scientific dogma. 3,5,6 Methods A through literature search was conducted in PubMed to gather the published articles comparing clinical outcomes of FTET and FET. The following keywords were used: 'frozenthawed embryo transfer', 'fresh embryo transfer', 'cryopreserved-thawed embryo transfer', 'freeze all policy', from their inceptions through July 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Research Article Laser collapse performance in blastocysts applied before vitrification Based on these facts, many centers have chosen to freeze all embryos to transfer them in a next cycle, method known as "Freeze-all strategy". 1,5,7,9 The first pregnancy obtained by transfer of frozen and thawed embryos was reported by Trouson and Mohr in 1983 and since then, the cryopreservation of embryos has been used as standard procedure in human reproduction clinics. [10][11][12] Thus, three main methods of cryopreservation have been employed: slow freezing, ultra fast freezing and vitrification.…”
Section: /7mentioning
confidence: 99%
“…However, the success of embryo implantation and decrease of perinatal morbidity depends not only on its quality, but also on the receptivity of the endometrium as well as the maternal microenvironment and embryonic signaling with the uterine cavity. 1,2 In IVF centers, more and more specialists have shifted to transference of frozen embryos (TEC), instead of fresh transfer. [3][4][5] This is due to the fact that the transfer of fresh embryos in patients with ovarian hyperstimulation syndrome (OHSS) can lead to death risk for the patient.…”
Section: Introductionmentioning
confidence: 99%